2022
DOI: 10.3390/cancers14225484
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Screening in Greece: A Modelling Study to Estimate the Impact on Lung Cancer Life Years

Abstract: (1) Background: Lung cancer causes a substantial epidemiological burden in Greece. Yet, no formal national lung cancer screening program has been introduced to date. This study modeled the impact on lung cancer life years (LCLY) of a hypothetical scenario of comprehensive screening for lung cancer with low-dose computed tomography (LDCT) of the high-risk population in Greece, as defined by the US Preventive Services Taskforce, would be screened and linked to care (SLTC) for lung cancer versus the current scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Unfortunately, rural Greek areas, as well as the Greek islands, are basically excluded from these efforts due to transportation issues. A study published in 2022 by Souliotis et al revealed that applying a 100% screening strategy among high-risk adults aged 50–80 would result in additional averted deaths and lung cancer life years gained over 5 years in Greece [ 91 ].…”
Section: Lung Cancer In the Greek Realitymentioning
confidence: 99%
“…Unfortunately, rural Greek areas, as well as the Greek islands, are basically excluded from these efforts due to transportation issues. A study published in 2022 by Souliotis et al revealed that applying a 100% screening strategy among high-risk adults aged 50–80 would result in additional averted deaths and lung cancer life years gained over 5 years in Greece [ 91 ].…”
Section: Lung Cancer In the Greek Realitymentioning
confidence: 99%